Influence of oral fatty applications on biochemical indicators of inflammation and dysbiosis in the tissues of the rat mouth - A. V. Markov; Iu. Z. Labush; I. V. Khodakov; A. P. Levitsky; G. N. Varava (Kazimierz Wielki University, 2018)
Background. The negative impact on the body of high-fat nutrition largely depends on the fatty acid composition of edible fats and the presence of peroxidation products in them, which are formed during heat treatment. Despite the considerable number of studies on this issue, it remains unclear the nature of the influence of different dietary fats on the condition of the tissues of the oral cavity. The purpose of this study was to clarify this issue Methods. Ordinary (high-linoleic) sunflower oil, high-oleic sunflower oil and butter in the native state and after heat treatment were used. The experiments were carried out on 35 white rats with an average weight of 252±15 g, who were given oral applications of the above fats at a dose of 0.5 ml per rat for 3 days. After rat killing on the 4th day, the content of malondialdehyde (MDA), the activity of elastase, urease, lysozyme and catalase were determined in the cheek mucosa homogenate and in the gums. The degree of dysbiosis was calculated by the ratio of the relative activities of urease and lysozyme. The antioxidant-prooxidant API index was calculated from the ratio of catalase activity and MDA content Results. Oral applications of native and heat-treated oils cause a decrease in the MDA content in both tissues with the exception of heat-treated butter, applications of which do not reduce the MDA level. Applications of heat-treated oils increase the activity of elastase in the gums, and heat-treated sunflower oil in the cheek mucosa. Applications of native and heat-treated oils reduce the activity of catalase in the cheek and gums. The API index increases in the gums under the action of native oils and decreases under the action of thermally processed oils. Applications of butter (native and heat-treated) significantly reduce the activity of urease in the cheek mucosa. Sunflower and high-oleic sunflower oils tend to increase the activity of urease, the least pronounced for the latter. All oils except high-oleic sunflower, reduce the activity of lysozyme in both tissues and all oils increase the degree of dysbiosis (except butter in the cheek mucosa). The content of diene conjugates after heat treatment increased the most in butter, and the least in high-oleic sunflower oil. Conclusion. Oral applications of fats cause a decrease in the formation of active forms of oxygen in the tissues of the oral cavity, which causes the development of dysbiosis and inflammatory processes.